2010
DOI: 10.1080/03014223.2010.496488
|View full text |Cite
|
Sign up to set email alerts
|

Conservation status, threats and management options for the Open Bay Island skink (Oligosoma taumakae)

Abstract: The Open Bay Islands are a Māori-owned Wildlife Refuge located in South Westland (South Island) and support two of the rarest lizard species in New Zealand: the Open Bay Island skink and the Open Bay Island gecko. Both species have been assigned a threat status of Nationally Critical Á the highest priority for conservation action. The terrestrial and diurnal habits of the skink make it particularly vulnerable to predation by wēkā, a flightless rail native to New Zealand but introduced to the Open Bay Islands c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Both the above species are small (mean and maximum SVLs reported for cryptic skink were 55 and 74 mm, respectively; Chapple et al 2011), whereas the Open Bay Island skink is much larger (maximum SVL of 96 mm; Lettink et al 2010). Among New Zealand lizards, extinction risk appears to increase with body size (Hitchmough et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Both the above species are small (mean and maximum SVLs reported for cryptic skink were 55 and 74 mm, respectively; Chapple et al 2011), whereas the Open Bay Island skink is much larger (maximum SVL of 96 mm; Lettink et al 2010). Among New Zealand lizards, extinction risk appears to increase with body size (Hitchmough et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, they can attract predators in search of shelter or prey, can be interfered with by people, livestock and native wildlife (e.g. Lettink et al 2010) and may alter the distribution, abundance and/or survival of animals using them if left out permanently (Lettink et al 2011;Batson et al 2015).…”
Section: Artificial Retreatsmentioning
confidence: 98%
“…They have been implicated in the extinction of the Macquarie Island parakeet (Cyanoramphus novaezelandiae erythrotis), which occurred after populations of cats (Felis catus) and weka increased in response to the introduction of rabbits (Oryctolagus cuniculus) (Taylor 1979); although weka impacts cannot be disentangled from those of cats and rabbits in this case. The extreme rarity of the Open Bay Islands skink (Oligosoma taumakae) and gecko (an undescribed species from the Mokopirirakau genus) has been attributed to weka predation (Lettink et al 2010). Weka were introduced to the Open Bay Islands in the early 1900s (Stirling & Johns 1969), and although weka have not been observed preying on either species, they have been observed hunting for skinks (Lettink et al 2010) and the skinks are now found mostly in habitat inaccessible to weka (Chapple & Patterson 2007).…”
Section: Impacts Of Weka On Native Speciesmentioning
confidence: 99%
“…The extreme rarity of the Open Bay Islands skink (Oligosoma taumakae) and gecko (an undescribed species from the Mokopirirakau genus) has been attributed to weka predation (Lettink et al 2010). Weka were introduced to the Open Bay Islands in the early 1900s (Stirling & Johns 1969), and although weka have not been observed preying on either species, they have been observed hunting for skinks (Lettink et al 2010) and the skinks are now found mostly in habitat inaccessible to weka (Chapple & Patterson 2007). Dramatic declines in mottled and Cook's petrel populations on Whenua Hou in the 1940s were attributed to weka predation, although kiore and possums were also present at the time (Blackburn 1968).…”
Section: Impacts Of Weka On Native Speciesmentioning
confidence: 99%